Association between availability of non-prescription beta 2 agonist inhalers and undertreatment of asthma. Issue 6891 (5th June 1993) - Gibson, P; Henry, D; Francis, L; Cruickshank, D; Dupen, F; Higginbotham, N; Henry, R; Sutherland, D
Abstract : OBJECTIVE--To determine whether the availability of beta 2 agonist inhalers without prescription leads to undertreatment of asthma. DESIGN--Cross sectional study of adequacy of treatment in asthmatic subjects who purchased beta 2 agonist inhalers and subjects who obtained inhalers by prescription. SETTING--Community pharmacies in New South Wales, Australia. SUBJECTS--403 eligible consecutive asthmatic subjects aged 13 to 55 purchasing salbutamol metered dose inhalers over the counter or by prescription; 197 attended for follow up and spirometry and 139 returned 14 day symptom, peak flow, and medication diaries. MAIN OUTCOME MEASURES--Severity of asthma assessed on frequency of day time and night time wheezing, frequency of inhaler use, and peak expiratory flow rates. Adequacy of treatment according to published guidelines. RESULTS--Of the 139 patients who completed the diary 83, (60%) purchased their inhalers without prescription and 83 were undertreated. The characteristics of patients in the prescription and purchasing groups were similar. Multiple logistic regression analysis identified use of non-prescribed salbutamol as being associated with a 2.9-fold increase in the odds of undertreatment (95% confidence interval 1.3 to 6.8). Smoking increased the odds of undertreatment (3.3, 1.2 to 9.5) and use of a peak flow meter reduced the odds (0.11, 0.04 to 0.34). Adjustment for frequency of consultation made use of non-prescription salbutamol insignificant (1.4, 0.55 to 3.8). Attitudes to services provided by doctors and pharmacists were favourable and not associated with undertreatment. CONCLUSION--Over the counter purchase of salbutamol is associated with infrequent consultation with doctors and undertreatment of asthma.